MEDIASI SEBAGAI SALAH SATU ALTERNATIF PENYELESAIAN SENGKETA : STUDI KASUS PENGADILAN AGAMA DI YOGYAKARTA - Nanang Andrianto; Syeh Assery; Suhartono Suhartono (National Conference on Applied Business, Education, & Technology (NCABET), 2022)
This study aims to understand and evaluate mediation as one of the factors for the achievement of the performance assessment of religious courts. The research method uses a descriptive qualitative approach with the data collection of interview, observation and documentation. The informants in the study were 3 who played a role in the mediation process at the Wates Religious Court in Yogyakarta. Data were analyzed by reduction, display, and verification. The results of the study found that (1) the success of mediation has not been maximized because there are partially successful and some are unsuccessful (2) factors inhibiting the mediation process are competency and discipline of the mediator in fulfilling the schedule. (3) Efforts to increase the success of mediation, namely by increasing the competence of the mediator and improving the discipline of the mediator. The leadership of the Religious Courts also needs to carry out monitoring and evaluation of the competence and discipline of the mediator and evaluate the mediation on an ongoing basis